Pengaruh Model SFAE Berorientasi Tri Hita Karana Terhadap Hasil Belajar IPA - Putra, I G. N. Pt. Adi Laksana (Universitas Pendidikan Ganesha, 2019)
This study aimed at investigating the effect of Student Facilitator and Explaining (SFAE) technique based on Tri Hita Karana towards students’ science achievement in fifth grade of Buleleng district primary schools cluster XV academic year 2017/2018. This study was an experimental study utilizing non-equivalent post-test only control group design. The population of this study was fifth graders of Buleleng district primary schools cluster XV and the sample of this study was fifth graders of SD Negeri 2 Kalibukbuk as the experimental group and fifth graders of SD Negeri 3 Anturan as the control group. The data collection was utilizing instrument in the form objective test. Then, the obtained data was analysis using both descriptive and inferential (t-test) statistical analysis. The result showed that there was a difference of mean score between both groups. The mean score for experimental group was 23,12 while the mean score for control group was 16,21. Furthermore, hypothesis testing showed that tobs>tcv (tobs=6,821 > tcv=1,99962). Based on the result of the study, it can be concluded that there was a significant difference on students’ science achievement between the students taught using Student Facilitator and Explaining (SFAE) technique based on Tri Hita Karana and the students taught without Student Facilitator and Explaining (SFAE) technique based on Tri Hita Karana at fifth graders of Buleleng district primary schools cluster XV academic year 2017/2018